A inteligência está la fora: notas sobre o design de rua - Paz, Daniel Juracy Mellado (2013)
ABSTRACT: The paper aims to recognize the intelligence that is scattered around us, good constructive solutions that appear in more common initiatives, albeit expressed in poor materials or poor conditions, exceeding the usual architect´s prejudice as the authorship and aspect. The attempt is to try to make professional´s boundaries permeable to the inspiration of the everyday design. The paper presents a synthesis of recent similar attempts, especially one that focuses on the seemingly ordinary. It is argued that quality and innovation are not the privilege of the professional and that cunning, spread in society, is indispensable, like a preparation of scenario, for the arising of recognized innovations. The signals of that cunning are pursued in the streets of Salvador, in the design of street vendors and in the beach huts (torn down in 2010) and the objects specifically designed to take advantage of the conditions of urban space. The lesson of such things occurs by suddenly revealing the gap between demand and built environment and even by the aesthetic and functional quality that its can have.